Implementasi Pembelajaran Luring pada Masa Pandemi Covid-19 Mata Pelajaran IPS Geografi di Kelas XI SMA Negeri Walea Besar - Yanna, Abdun; Nurvita; Hasdin (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
The purpose of this study was to determine the Implementation of Offline Learning during the Covid-19 Pandemic for Social Studies Geography subjects in class XI SMA Negeri Walea Besar. The subject of this research is the geography teacher of class XI IPS. This study uses a descriptive qualitative approach. In an effort to provide answers to the problems raised. Data were collected through observation, interviews, and documentation. The results showed that the implementation of Offline Learning was less effective, but in the process of delivering material to students, it was achieved. In addition, during the meeting, the teacher not only delivered learning material but also the teacher gave assignments to students according to the material being studied and taught to be done at home. a form of mastery learning assessment or complete learning. The results of the homework given by the Social Sciences Geography teacher for class XI from 12 students, in fact, there are still 4 people who are late to deliver homework and others on time, and there are still students who have not received the standard of completeness scores. In contrast, the inhibiting factors for teaching and learning activities are transportation costs, distance to study, learning time, the risk of contracting Covid-19, limited knowledge of technology, and the targets set for learning. The supporting factors are facilities and infrastructure, student health, weather factors, learning limitations, and health protocols.